Smoking Behavior of Officials in TGK Chik Ditiro Hospital in Pidie 2018 - Marsullita, Marsullita (Sari Mutiara Indonesia University Press, 2018)
Supports for the formation of smoke-free area that reflect in the place, is very necessary. Considering cigarettes are among the top ten causes of death in the world and classified as the single largest cause of death, reaching 7 million people, where 6 million more occur in active smokers and the rest are passive smokers. The cause of death was mainly due to lung and liver cancer, the cause of the low-middle income countries facing this double burden because they had the highest number of smokers. This study aims to determine the smoking behavior of officers in the public hospital area of Tg Chik Ditiro in district Pidie. This study uses Qualitative research design with phenomenological study design by taking five informants. Data collection uses the interview guidelines and the researchers themselves as a data collection tool conducted from June 6th to July 20th, 2018 at Tgk Chik Ditiro, district Pidie. The results showed that predisposing factors (normative values and trust), enabling factors (application of smoking regulations in public facilities), reinforcing factors (co – workers, leaders) and motivational factors (pleasure, performance enhancements which became the basis of informants found it difficult to apply smoking Tg Chik Ditiro Hospital in district Pidie. The writer suggests that normative values, application of regulations, co-workers, leaders support behavioral changes to stop smoking and provide a program to stop tobacco addiction because of the effects of pleasure and increased focus on tobacco use